An Investigation into Linguistic Expressions of Interpersonal Meaning and Their Translational Equivalents in the Tale of Kieu and its English Version - Nguyen Thi Ly Thao
Chapter 1.Introduction; Chapter 2.Literature review and theoretical background; Chapter 3.Methods and procedues; ...